TERT Promoter Methylation Is Oxygen-Sensitive and Regulates Telomerase Activity - Dogan, Fatma; Forsyth, Nicholas R. (Biomolecules (Basel, Switzerland), 2024)
Telomere repeats protect linear chromosomes from degradation, and telomerase has a prominent role in their maintenance. Telomerase has telomere-independent effects on cell proliferation, DNA replication, differentiation, and tumorigenesis. TERT (telomerase reverse transcriptase enzyme), the catalytic subunit of telomerase, is required for enzyme activity. TERT promoter mutation and methylation are strongly associated with increased telomerase activation in cancer cells. TERT levels and telomerase activity are downregulated in stem cells during differentiation. The link between differentiation and telomerase can provide a valuable tool for the study of the epigenetic regulation of TERT. Oxygen levels can affect cellular behaviors including proliferation, metabolic activity, stemness, and differentiation. The role of oxygen in driving TERT promoter modifications in embryonic stem cells (ESCs) is poorly understood. We adopted a monolayer ESC differentiation model to explore the role of physiological oxygen (physoxia) in the epigenetic regulation of telomerase and TERT. We further hypothesized that DNMTs played a role in physoxia-driven epigenetic modification. ESCs were cultured in either air or a 2% O2 environment. Physoxia culture increased the proliferation rate and stemness of the ESCs and induced a slower onset of differentiation than in ambient air. As anticipated, downregulated TERT expression correlated with reduced telomerase activity during differentiation. Consistent with the slower onset of differentiation in physoxia, the TERT expression and telomerase activity were elevated in comparison to the air-oxygen-cultured ESCs. The TERT promoter methylation levels increased during differentiation in ambient air to a greater extent than in physoxia. The chemical inhibition of DNMT3B reduced TERT promoter methylation and was associated with increased TERT gene and telomerase activity during differentiation. DNMT3B ChIP (Chromatin immunoprecipitation) demonstrated that downregulated TERT expression and increased proximal promoter methylation were associated with DNMT3B promoter binding. In conclusion, we have demonstrated that DNMT3B directly associates with TERT promoter, is associated with differentiation-linked TERT downregulation, and displays oxygen sensitivity. Taken together, these findings help identify novel aspects of telomerase regulation that may play a role in better understanding developmental regulation and potential targets for therapeutic intervention.